“Neo-catholic” M. E. Zdziechowski and L. N. Tolstoy: a history of their acquaintance and the evolution of M. E. Zdziechowski’s attitude to the “christian anarchism” of L. N. Tolstoy - Irina Vorontsova (Vestnik Pravoslavnogo Svâto-Tihonovskogo Gumanitarnogo Universiteta: Seriâ II. Istoriâ, Istoriâ Russkoj Pravoslavnoj Cerkvi)
Slavist and Polish Slavophil M.E. Zdzekhovsky came to the attention of Russian scientists relatively recently and has not yet taken its due place in domestic research. 2023 marks the 85th anniversary of his death. A Pole by origin, baptized in the Catholic faith, he remained a representative of a single space of the Slavic world and was close to that part of the Polish and Russian intelligentsia, which at the beginning of the 20th century began to be called "religious", since it put the question at the center of its worldview. about the necessity for the social development of states - religious consciousness. At the end of the XIX century. Zdzekhovsky became an admirer of L.N. Tolstoy, and then imbued with his teaching on the moral essence of Christianity. Having taken the post of professor at the University of Krakow and having moved to Austria-Hungary, Zdziechovsky continued his epistolary communication with the Russian intelligentsia and with L.N. Tolstoy, whom he called his teacher. He carried a respectful attitude towards the writer through the years of his passion for modernism (1890-1914) in the Roman Catholic Church, contact with which he found in Tolstoy's moralism. The article, based on letters and books (1890–1914) by Zdziechowski, analyzes the evolution of the attitude of the Polish “neo-Catholic” towards Tolstoy as a thinker. Not accepting Tolstoy's "Christian anarchism", Zdziechowski did not condemn his apostasy from the Church, putting the moral aspect of his search, based on epistemological pessimism, at the center of his understanding of Tolstoy's phenomenon. The author concludes that M.E. Zdziechowski's work of the writer and the moral apology of Christianity in modernism, played a leading role in Zdziechowski's attitude towards Tolstoy.